Public, trade union and cooperative enterprise in Germany : the commonweal idea - Hesselbach, Walter (London : Cass, 1976)
This book provide the history, theory and the activities of the most important commonweal enterprise of the German workers
Translation of Die gemeinwirtschaftlichen Unternehmen.
Includes bibliographical references and index.
oo 24/01/2019
Loans
Keywords: Cooperation; Labor union-owned business enterprises